Being a refugee in Turkey and western Europe: how it affects mental health and psychosocial wellbeing. Issue 2 (July 2016) - Unknown
Abstract : In this personal reflection, the author is a Syrian refugee who describes his experiences as a psychosocial worker in Syria and with refugees in Turkey and Greece. He highlights how women and children lack safety in the camps. The second section discusses how he became a refugee himself. Due to his experiences in Syria, he now finds himself in a difficult situation in the Netherlands, the county where he applied for asylum and has received a permit, but his 'cry for help' remains unheard and unrecognised by the (health) workers in the asylum centre.